THE DIFFERENCES OF PHYSICAL, CHEMICAL AND FATTY ACID PROFILE OF MEAT QUALITY OF MALE MUSCOVY (Cairina moschata) AND LOCAL DUCK (Anas plathyrinchos) - Ismoyowati, I.; Iriyanti, N.; Santosa, A. (Diponegoro University, 2012)
This research was aimed to differentiate the meat physical, chemical and fatty acid profile qualityin muscovy and other local ducks (Magelang, Tegal and mojosari). Completely Randomized Design wasused in this study. Breed used as treatments was muscovy, Magelang, Tegal and Mojosari ducksrepeated 5 times. Analysis of variance and honestly significant difference were used to analyze data.Result showed there were differences in physical quality of meat in the term of colour, pH, and cookingloss, while water holding capacity and tenderness were relatively similar. Fat, cholesterol and proteinwere relatively similar. Muscovy duck has a higher polyunsaturated fatty acids (PUFAs) than the otherlocal duck. In conclusion, the physical and chemical quality of meat of muscovy and other local duckswere silimar. Muscovy duck meat is healthier to consume due to a higher polyunsaturated fatty acidsthan the other local ducks.